Molecular phylogenetics of a recently isolated goat pox virus from Vietnam - Trang, Hong Pham; Abdul Rahaman, Nor Yasmin; Mohd Lila, Mohd Azmi; Huong, Lan Thi Lai; Lan, Thi Nguyen; Giap, Van Nguyen; Bo, Xuan Ha; Nguyen, Hieu; Hanh, Duc Vu; M. Noordin, Mustapha (BMC, 2021)
Background: After a decade of silence, an outbreak of the contagious and Asian endemic disease, goat pox reemerged in North Vietnam affecting more than 1800 heads with a mortality rate of 6.5%. The inevitable impact of goat pox on hide quality, breeding, chevon and milk production has resulted in a significant economic losses to the developing goat industry of Vietnam. In the act of establishing an effective control of this devastating disease, tracing the source of re-emergence via a phylogenetic study was carried out to reveal their genetic relatedness. Either skin scab or papule from the six affected provinces were collected, cultured into Vero cells followed by restricted enzyme digestion of targeted P32 gene DNA encoding. The P32 gene was then cloned and transformed into E.coli competent cells for further sequencing. Results: The isolated sequence is deposited into GenBank under Accession No. MN317561/VNUAGTP1. The phylogenetic tree revealed high similarity of nucleotide and amino acid sequences to references goat pox strains accounting for 99.6 and 99.3, respectively. The Vietnamese strain is clustered together with currently circulating goat pox virus in China, India and Pakistan which suggested the origin of South China. Conclusions: This Vietnam isolate is clustered together with other Asian goat pox strains indicating the dissemination of a common goat pox virus within this continent.